Math Problem Statement

obtaine pdnf of (p->q) ^ (p <->r) without using truth table

Solution

To obtain the Principal Disjunctive Normal Form (PDNF) of the expression (pq)(pr)(p \to q) \land (p \leftrightarrow r) without using a truth table, we need to proceed through logical manipulations. Here's a step-by-step process:

Step 1: Express the implications and biconditional in terms of basic logical connectives.

  • The implication pqp \to q can be rewritten as: pq¬pqp \to q \equiv \neg p \lor q

  • The biconditional prp \leftrightarrow r can be rewritten as: pr(pr)(¬p¬r)p \leftrightarrow r \equiv (p \land r) \lor (\neg p \land \neg r)

Thus, the original expression becomes: (¬pq)((pr)(¬p¬r))(\neg p \lor q) \land ((p \land r) \lor (\neg p \land \neg r))

Step 2: Apply distribution of conjunction over disjunction.

We distribute (¬pq)(\neg p \lor q) over (pr)(¬p¬r)(p \land r) \lor (\neg p \land \neg r), using the distributive law of logic: A(BC)(AB)(AC)A \land (B \lor C) \equiv (A \land B) \lor (A \land C)

So, (¬pq)((pr)(¬p¬r))((¬pq)(pr))((¬pq)(¬p¬r))(\neg p \lor q) \land ((p \land r) \lor (\neg p \land \neg r)) \equiv ((\neg p \lor q) \land (p \land r)) \lor ((\neg p \lor q) \land (\neg p \land \neg r))

Step 3: Simplify each conjunction.

First term: (¬pq)(pr)(\neg p \lor q) \land (p \land r)

  • Distribute (¬pq)(\neg p \lor q) over (pr)(p \land r): (¬pq)(pr)(¬ppr)(qpr)(\neg p \lor q) \land (p \land r) \equiv (\neg p \land p \land r) \lor (q \land p \land r)

  • The term ¬pp\neg p \land p is always false, so it simplifies to: (qpr)(q \land p \land r)

Second term: (¬pq)(¬p¬r)(\neg p \lor q) \land (\neg p \land \neg r)

  • Distribute (¬pq)(\neg p \lor q) over (¬p¬r)(\neg p \land \neg r): (¬pq)(¬p¬r)(¬p¬p¬r)(q¬p¬r)(\neg p \lor q) \land (\neg p \land \neg r) \equiv (\neg p \land \neg p \land \neg r) \lor (q \land \neg p \land \neg r)

  • The term ¬p¬p¬r\neg p \land \neg p \land \neg r simplifies to: ¬p¬r\neg p \land \neg r

  • So the whole expression becomes: (¬p¬r)(q¬p¬r)(\neg p \land \neg r) \lor (q \land \neg p \land \neg r)

Step 4: Combine the results.

Now, we combine the two simplified terms from Step 3: (qpr)(¬p¬r)(q¬p¬r)(q \land p \land r) \lor (\neg p \land \neg r) \lor (q \land \neg p \land \neg r)

Step 5: Further simplifications (if any).

Observe that (q¬p¬r)(q \land \neg p \land \neg r) is already included in (¬p¬r)(\neg p \land \neg r) because ¬p¬r\neg p \land \neg r doesn't depend on qq. So, the term q¬p¬rq \land \neg p \land \neg r is redundant and can be removed.

Thus, the final PDNF is: (qpr)(¬p¬r)(q \land p \land r) \lor (\neg p \land \neg r)

This is the Principal Disjunctive Normal Form (PDNF) of the expression (pq)(pr)(p \to q) \land (p \leftrightarrow r).


Do you have any questions or would you like more details on any step?

Related Questions:

  1. What is the difference between PDNF and CNF?
  2. How do we simplify logical expressions using Karnaugh maps?
  3. Can the logical equivalence (pr)(p \leftrightarrow r) be simplified differently?
  4. How do we handle implications and biconditionals in logical expressions?
  5. What is the role of distributive and associative laws in simplifying Boolean expressions?

Tip:

Always break down logical connectives into simpler forms (like AND, OR, and NOT) when transforming expressions into PDNF or CNF to make distribution and simplification easier.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Propositional Logic
Disjunctive Normal Form (DNF)
Implication
Biconditional

Formulas

Implication: p -> q ≡ ¬p ∨ q
Biconditional: p <-> r ≡ (p ∧ r) ∨ (¬p ∧ ¬r)
Distributive Law: A ∧ (B ∨ C) ≡ (A ∧ B) ∨ (A ∧ C)

Theorems

Distributive Law of Conjunction over Disjunction

Suitable Grade Level

College-Level Logic or Discrete Mathematics